L-Fuzzy Semiprime Ideals of a Poset - Berhanu Assaye Alaba; Derso Abeje Engidaw (Advances in Fuzzy Systems)
In this paper, we introduce the concept of L-fuzzy semiprime ideal in a general poset. Characterizations of L-fuzzy semiprime ideals in posets as well as characterizations of an L-fuzzy semiprime ideal to be L-fuzzy prime ideal are obtained. Also, L-fuzzy prime ideals in a poset are characterized.